CAPITAL MANAGEMENT IN ISLAMIC ECONOMY - EVA ANDRIANI (Universal Institute of Professional Management, 2023)
Everything that appears in human life has a law that surrounds it. All the rules that have been brought by Rasulullah SAW aim to make human life always conducive in accordance with the mandate that has been determined by Allah SWT. Commerce, which is an effort to develop capital, is a practice recommended in religion so that human life continues to develop and does not stagnate. Included in commerce is the importance of capital management. In this case, there are rules to ensure that capital always develops and is regulated in such a way that efforts to develop capital are always optimal. Moreover, the profits earned become blessed and beneficial. This qualitative article attempts to explore capital management from the perspective of Islamic law. Based on a series of studies that have been reviewed, the findings of this article can be summarized as follows: Capital management is a series of efforts to ensure that capital develops optimally. The scope of capital development has been regulated by Sharia with the aim of ensuring that capital continues to develop optimally, and that the profits earned are both beneficial and blessed.